The individual in the community: Horace Kallen, cultural pluralism and the making of the early adult education movement - Amy D. Rose; Linda O’Neill (Adult Education Research Conference, 1995)
This paper examines the work of Horace Kallen in light of his interest in individualism, the community, and the meaning of cultural pluralism. This work is then discussed in terms of its relationship to early adult education.